(NbEDNYE L@DI(B: [(NrOMAN(B] /s - (NdOSTOEWSKIJ(B, (NfEDORs ((NmOSKWA(B:s (Nast(B,s, 2005)
(Nw KNIGU WO[LI ROMANY (B"(NbEDNYE L@DI(B", "(NbELYE NO^I(B" (NI (B"(NnETO^KA nEZWANOWA(B", (NPOWESTX (B"(NdQD@[KIN SON (B", (NA TAKVE RASSKAZY ~UVAQ VENA I MUV POD KROWATX@ I (B"(N~ESTNYJ WOR(B"s
rus
Keywords: (N|PISTOLQRNYJ ROMANs; (NpOWESTI I RASSKAZYs